Evaluation of cytokine levels using QuantiFERON-TB Gold Plus in patients with active tuberculosis. Issue 5 (May 2020) - Suzukawa, Maho; Takeda, Keita; Akashi, Shunsuke; Asari, Isao; Kawashima, Masahiro; Ohshima, Nobuharu; Inoue, Eri; Sato, Ryota; Shimada, Masahiro; Suzuki, Junko; Yamane, Akira; Tamura, Atsuhisa; et al.
Highlights: QFT-plus did not enhance cytokine production vs. QFT-3 G. PDGF-BB was higher in the TB2 tube than the TB1 tube in QFT-plus. IL-6 and TNF-α were higher in the TB1 tube than the TB2 tube in QFT-plus. IP-10 in QFT-3 G and QFT-plus were useful for diagnosing active tuberculosis. IFN-γ, IL-1RA, IL-2, IP-10, MCP-1 and MIP-1β were higher in tuberculosis patients than in the healthy controls. Abstract: Objectives: A recently released new QuantiFERON (QFT) product, QFT TB Gold plus (QFT-plus), is optimized for both CD4 and CD8 responses and reported to have higher sensitivity compared to the former QFT-3 G. Previously, using supernatants of QFT-3 G, we and others have demonstrated that cytokines other than IFN-γ may be useful in diagnosing tuberculosis. The present study aimed to identify cytokines that are useful for accurately diagnosing active tuberculosis by using QFT-plus and compared the data to those with QFT-3 G. Methods: Eighty-three active tuberculosis patients and 70 healthy control subjects who were examined by QFT at Tokyo National Hospital from June 2017 to July 2018 were enrolled. QFT-3 G and QFT-plus were performed according to the manufacturer's instructions. At the same time, blood cell culture supernatants were collected and assayed for their cytokine levels using R&D Systems Luminex Assay and MAGPIX System. The levels of cytokines were compared between different antigen-containing tubes (3 G Ag, TB1 and TB2 tubes), as well as between the patients and the control subjects. ROC curves were drawn, and the AUCs were calculated. Results: Five cytokines, i.e., IL-2, IL-6, IL-8, IP-10 and MIP-1β, produced by human blood cells in three independent tubes containing different tuberculosis antigens were higher in the 3 G Ag tube compared to both the TB1 and TB2 tubes. Further, when the TB1 and TB2 tubes were compared, TB2 showed greater production of only PDGF-BB, and less production of IL-6 and TNF-α. For diagnosing active tuberculosis, the levels of IP-10 were superior to the level of IFN-γ based on showing a larger AUC for ROC curves in our present study setting. Finally, the levels of IFN-γ, IL-1RA, IL-2, IP-10, MCP-1 and MIP-1β were distinctly different between the active tuberculosis patients and healthy controls. Conclusions: In summary, there was no cytokine that was higher in the tubes of QFT-plus compared to the tube of QFT-3 G, suggesting inferiority of QFT-plus antigens to 3 G Ag in terms of elicitation of cytokine production. Our results also suggest the usefulness of cytokines that showed a significant difference between the active tuberculosis patients and the healthy controls—namely, IFN-γ, IL-1RA, IL-2, IP-10, MCP-1 and MIP-1β—for diagnosing tuberculosis, but the roles of these cytokines in the pathogenesis of tuberculosis need to be elucidated (UMIN000035253).